RESEARCH OF SURFACE MORPHOLOGY OF A SYNTHED INHIBITOR BASED ON MALEINE ANGIIRIDID (International conference on multidisciplinary science, 2024)
In this article, the corrosion inhibitor synthesized based on maleic anhydride, monoethanolamine, and phosphoric acid to determine the mechanisms of steel inhibition are studied. This shows that the inhibitor protect steel at a high level in various aggressive environments. Its effect on the steel surface using a scanning electron microscope.